Makna Biaya Operasional Bagi Petani Tambak Di Lamongan - Mutiara Indah Dewi Aisah; Rahmat Agus Santoso (YUME : Journal of Management, 2022)
Abstrak This research has a problem, namely fish pond farmers in Lamongan still use manual feed such as rice mambu, snails, and crabs. This can cause most fish to not develop properly, thus affecting the income of each farmer. The focus of research is using Supply Chain Management which is needed by fish pond farmers in Lamongan to help manage the process of developing aquaculture. Fish pond farmers in Lamongan carry out supply chain management practices specifically in terms of automation, nursery technology, and site selection. In this study the aim was to find out the meaning of operational costs for fish pond farmers in Lamongan using 30 informants through interviews to get the meaning of operational costs. This research uses qualitative methods. Miles and Huberman's (1984) interactive method, namely data collection, reduction, presentation, and verification are used as data analysis techniques. Based on the research results, operational costs are significant because they affect the amount of income and profits of pond farmers in Lamongan. Kata Kunci: Cultivation; Fish farmers; Operating costs.